TECTONOSTRATIGRAPHY AND SEDIMENTATION PATTERN OF BS SUBBASIN, CENTRAL SUMATERA BASIN - SATRIO BASKORO (NIM : 12010101); Dosen Pembimbing: Dr. Ir. Dardji Noeradi, ANINDITO
BS Subbasin is located at Central Sumatera Basin that is proven in producing hydrocarbon in Indonesia. This research aims to analyze the tectonostratigraphy and sedimentation pattern of the research area, focused on syn-rift deposition of Pematang Group and also to interpret its depositional environment. Pematang Group consists of Lower Red Beds Formation, Brown Shale Formation, and Upper Red Beds Formation. The main structure pattern of the research area is normal fault with NNW-SSE trends. This research uses datas such as well log data, seismic 2D, and lithology description reports. The methods that are used in this research are determination of formation interval in Pematang Group, correlation of top formations, well-seismic tie, seismic 2D interpretation, making of time structure maps, interpretation of depositional environments, flattening, making of isochrone maps, making of Root Mean Square (RMS) Amplitude maps, and analysis of tectonostartigraphy and sedimentation pattern of each tectonic phase from Pematang Group. Based on the research it is summarized that the Tertiary basin evolution in the research area was marked by rift process resulting half graben structure with NNW-SSE trend. Basin geometry and its sedimentation show the tectonic process that controlling the rift basin development was extentional tectonic with ENE-WSW trend caused by NNW-SSE border fault. Generally, basin rift on the research area can be interpreted as a failed rift basin marked by its syn-rift and post-rift phases. Syn-rift phase deposition can be divided into three phases which are early syn-rift, rift climax, and late syn-rift. Lithostratigraphically it was included on Pematang Group. In early syn-rift phase (Early Eocene-Middle Eocene), Lower Red Beds Formation with lithology of claystone, siltstone, and sandstone is deposited on lacustrine depositional environment with depositional facies of deltaic, lacustrine turbidit, and alluvial fans. In rift climax phase (Middle Eocene-Late Oligocene), Brown Shale Formation with lithology of shale, siltstone, and sandstone is deposited on lacustrine depositional environment with depositional facies of lacustrine turbidit and alluvial fans. In late syn-rift (Late Oligocene- Early Miocene), Upper Red Beds Formation with lithology of sandstone, conglomerate, and claystone is deposited on lacustrine depositional environment with depositional facies of fluvial, lacustrine turbidit, and alluvial fans. BS Subbasin had been deformated in F1 Deformation Periods (Eocene-Oligocene) caused by extentional tectonic with ENE-WSW trend that reactivates the previous structures on F0 Deformation Periods (pre-Tertiary).